Impact of gender on sexual problems and perceptions among urban Malay elderly in Malaysia - Minhat, Halimatus Sakdiah; Mat Din, Hazwan; Ramachandran, Vasudevan; Raja Adnan, Raja Nurzatul Efah; Ibrahim, Rahimah (Elsevier Ireland, 2019)
Background: Physical and pathological changes associated with advancing age affect sexual behaviours of the elderly. The aim of this study was to explore the impact of gender on sexual problems and perceptions among the urban Malay elderly. Methods: A cross-sectional study was conducted among 160 Malaysian elderly participants aged 60 years and older who live in Kuala Lumpur. Twelve neighbourhood associations were randomly selected using multi-stage cluster sampling. Data was collected using standardized and validated questionnaire by face-to-face interview technique with which was conducted by trained interviewers. Results: Mean age of the participants was 65.33 (5.87) year old with majority were still married. Female (55.7%) reported more sexual problems as evidenced by the higher proportion of those with lacked interest in having sex (72.5%), find sex is unpleasant (34.8%) and unable to come to orgasm (55.1%). Gender was found to have significant impact on every model obtained in the analysis for both sexual problems and perceptions. Female elderly were 10.6 times more likely to have sexual problem compared to male elderly (OR=10.64, P < 0.001, 95% CI 3.61, 31.35) and 033 less likely to have good sexual perception (OR=0.33, P=0.027, 95% CI 0.12,0.88). Conclusion: Gender is a crucial factor towards sexual problem and perceptions among older persons. Older women were reported to have more sexual problems and poor sexual perceptions, reflecting the needs for sexual awareness and education to improve the perceptions and sexuality in later life..